National Assessment at West Tanjung Jabung 2 Public High School (Teachers’ Perspective) - Asmaida, Asmaida (STAI Auliaurrasyidin Tembilahan, 2023)
This study aims to describe the teachers’ perspective towards the National Assessment at State Senior High School 2 Tanjung Jabung Barat. This research was qualitative descriptive that describes or expresses in words (qualitatively). Data was collected by interviewing the teachers. The results of this study indicate that: The teacher's understanding of the national assessment is quite good, this can be seen from the teacher's knowledge regarding the national assessment and the results of teacher interviews regarding the teacher's views on the national assessment policy. Besides that, the teacher's knowledge of the reasons the government established the national assessment policy, which in this case, allows the teacher to play a very important role in the national assessment. However, the teacher's knowledge regarding minimum competency assessment, character surveys, and learning environment surveys are quite good. The Implementation of the national assessment in teaching and learning activities have been carried out. (2) obstacles were the lack of student motivation, lack of student ability, and lack of outreach and training for teachers.